Characterization of Lactic Acid Bacteria from Budu Fish as Probiotic Candidates from Padang Pariaman Regency - Prima, Heppy Setya; Kudus Susalam, Malikil Alam; Maulana, Fajri Fajri; fajri, fadhli fadhli (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
West Sumatra is an area that has a large number of fermented food products, one of which is fermented fish called Budu. The purpose of this study was to isolate and identify Lactid Acid Bacteria isolates from Budu fish from Padang Pariaman Regency and evaluate their probiotic potential. The research method is as follows: isolation of Lactid Acid Bacteria from Budu fish, followed by assessment of resistance tests to gastric pH and bile salts and antimicrobial activity. Then, 16S rRNA was used to assess the species of lactic acid bacteria isolates. Of the 10 samples, one sample of Isolate MKS4, with potential antimicrobial activity was reported. The results showed that the morphological and biochemical characteristics of Lactid Acid Bacteria include Gram-positive bacteria, bacilli and catalase negative included in the homofermentative bacteria group. The greatest antimicrobial activity was shown by Escherichia coli MKS4 0157:H7 (14.79 mm), S. aureus ATCC 25923 (14.89 mm) and enteritidis ATCC 13076 (16.64 mm). The results of molecular identification using 16S rRNA showed that the isolated lactic acid bacteria had similarities with the Lactobacillus strain parabucneri strain HBUAS56106, namely antimicrobial potential against pathogenic bacteria. Lactobacillus. parabucneri strain HBUAS56106 can be used as an antidiarrheal agent and the best antimicrobial compound is classified as a probiotic bacteria